2010
DOI: 10.1021/ma100067x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Degradation of Starch, a Highly Branched Polymer, during Extrusion

Abstract: An investigation of the mechanisms of degradation of a branched polymer in extrusion was performed using starch as substrate. Starch has the advantage that the distribution of degree of polymerization of individual branches can be readily obtained using a debranching enzyme and also that it does not undergo any reaction except scission during extrusion, thereby aiding mechanistic interpretation. Various starches, containing a range of the highly branched amylopectin component and the much less branched amylose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
151
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 251 publications
(171 citation statements)
references
References 48 publications
10
151
0
3
Order By: Relevance
“…High-amylose starch has some special properties, such as its heat resistance [12], which is reflected by high gelatinization temperature and the retainment of granules in boiling water [13][14][15], and its digestion resistibility [16][17], due to which this starch has been used as resistant starch and in drug delivery systems. In addition, high-amylose starch is especially suitable for producing thermoplastic materials [18][19], because amylose as a linear molecule can provide better mechanical properties resulting from easier formation of crystallites and entanglements.…”
Section: Introductionmentioning
confidence: 99%
“…High-amylose starch has some special properties, such as its heat resistance [12], which is reflected by high gelatinization temperature and the retainment of granules in boiling water [13][14][15], and its digestion resistibility [16][17], due to which this starch has been used as resistant starch and in drug delivery systems. In addition, high-amylose starch is especially suitable for producing thermoplastic materials [18][19], because amylose as a linear molecule can provide better mechanical properties resulting from easier formation of crystallites and entanglements.…”
Section: Introductionmentioning
confidence: 99%
“…The most straightforward is simple reduction in size of the whole molecule. Studies on the evolution of both Level 2 and Level 1 structures during these processes [94,95] show first that amylopectin is preferentially degraded compared with amylose, which is unsurprising because of its larger size. In addition, it is found that this degradation brings the starch down to a maximum stable size (which depends on the mechanical conditions).…”
Section: Some Structure-property Relationsmentioning
confidence: 99%
“…There are two kinds of starch polymers, i.e., amylose and amylopectin (Jiang, Gao, Li & Zhang, 2011;Liu, Halley & Gilbert, 2010). These two biopolymers are organized on multiple scales in the starch granule to form its semicrystalline structure, including the whole granule, the growth rings, the semicrystalline lamellae and the crystallites (Buleon, Colonna, Planchot & Ball, 1998;Luengwilai & Beckles, 2009;Perez & Bertoft, 2010;Pikus, 2005;Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%